2022
DOI: 10.3389/fsurg.2022.1004687
|View full text |Cite
|
Sign up to set email alerts
|

Novel peripheral blood parameters as predictors of neoadjuvant chemotherapy response in breast cancer

Abstract: The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune severity index (SII), and prognostic nutritional index (PNI) are associated with the prognosis of gastric, lung, and breast cancers. However, the predictive value of pathological complete response (pCR) rates in patients with breast cancer treated with neoadjuvant chemotherapy (NAC) remains unclear. This retrospective study explored the correlation between each index and the efficacy of neoadjuvant chemotherapy in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Nineteen studies with 4301 patients reported the correlation between the PLR and pCR 22 26 28 32–40 42–47. Our results indicate that high PLR level was significantly associated with low pCR rate (HR 0.77, 95% CI 0.67 to 0.88, p<0.001), and significant heterogeneity was observed (I 2 =75.80%, P h <0.001, table 1, figure 1).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Nineteen studies with 4301 patients reported the correlation between the PLR and pCR 22 26 28 32–40 42–47. Our results indicate that high PLR level was significantly associated with low pCR rate (HR 0.77, 95% CI 0.67 to 0.88, p<0.001), and significant heterogeneity was observed (I 2 =75.80%, P h <0.001, table 1, figure 1).…”
Section: Resultsmentioning
confidence: 62%
“…Different studies use variant cut-off values from different methods. Traditionally, we believe that the ROC curve is the most suitable for getting the optimal cut-off value 33 41 43 46 47. However, other studies have also achieved significant results using the cut-off values from previous studies 26 28 34.…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving over 1100 patients found that pre-treatment PNI was a reliable predictor of pCR in breast cancer patients 54 . However, in the study by Yang et al, it was observed that pCR was not a predictive marker in breast cancer patients receiving PNI and NACT 55 . Lastly, a study by Oba T. divided patients receiving NACT into two groups based on their PNI before treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Earlier studies have shown that markers of inflammation, like NLR and PLR, could potentially serve as predictive factors for pCR following NACT in breast cancer (10)(11)(12)(16)(17)(18). Nevertheless, while these studies primarily examined the initial or pre-treatment condition of inflammatory markers, only a limited number of studies assessed the changes of inflammatory markers throughout or following the treatment.…”
Section: Discussionmentioning
confidence: 99%